A versatile and convenient tool for regulation of DNA strand displacement and post-modification on pre-fabricated DNA nanodevices. Issue 1 (20th December 2022) - Liao, Yangwei; Hu, Hao; Tang, Xiaofeng; Qin, Yang; Zhang, Wei; Dong, Kejun; Yan, Bei; Mu, Yaoqin; Li, Longjie; Ming, Zhihao; Xiao, Xianjin
Abstract: Toehold-mediated strand displacement and its regulatory tools are fundamental for DNA nanotechnology. However, current regulatory tools all need to change the original sequence of reactants, making the regulation inconvenient and cumbersome. More importantly, the booming development of DNA nanotechnology will soon promote the production of packaged and batched devices or circuits with specified functions. Regarding standardized, packaged DNA nanodevices, access to personalized post-modification will greatly help users, whereas none of the current regulatory tools can provide such access, which has greatly constrained DNA nanodevices from becoming more powerful and practical. Herein, we developed a novel regulation tool named Cap which has two basic functions of subtle regulation of the reaction rate and erasability. Based on these functions, we further developed three advanced functions. Through integration of all functions of Cap and its distinct advantage of working independently, we finally realized personalized tailor-made post-modification on pre-fabricated DNA circuits. A pre-fabricated dual-output DNA circuit was successfully transformed into an equal-output circuit, a signal-antagonist circuit and a covariant circuit according to our requirements. Taken together, Cap is easy to design and generalizable for all strand displacement-based DNA nanodevices. We believe the Cap tool will be widely used in regulating reaction networks and personalized tailor-made post-modification of DNA nanodevices. Graphical Abstract: